Competition Clauses in Bilateral Trade Treaties: Analysing the Issues in the Context of India's Future Negotiating Strategy - Sanghamitra Sahu (Indian Council for Research on International Economic Relations (ICRIER), 2008)
There is a recent trend towards trade agreements that include trade related competition provisions. However there are large differences across these trade agreements in terms of how the competition provisions are addressed. In this context, this research report tries to analyse the competition provisions in few selected FTAs and draw lessons for India, which is also following the path of entering into trade agreements. The analysis suggests that cooperation in implementing competition laws is immensely helpful. However, at this moment, India can follow the EU style of agreements with competition provisions such as cooperation, exchange of non-confidential information, technical assistance and consultation.
Keywords: 330; Handelsabkommen; Wettbewerbspolitik; Indien